Numerical modeling of microplastic interaction with fine sediment under estuarine conditions. (1st March 2023) - Shiravani, G.; Oberrecht, D.; Roscher, L.; Kernchen, S.; Halbach, M.; Gerriets, M.; Scholz-Böttcher, B.M.; Gerdts, G.; Badewien, T.H.; Wurpts, A.
Highlights: A new approach for determining the settling velocity of microplastic particles. Microplastic-fine sediment interaction through five settling velocity regions. 3D-numerical Modelling of microplastic transport in the tidal Weser river. Higher probability of small microplastic to pass the estuary and reach the open sea. Higher microplastic concentration in the estuarine turbidity zone. Abstract: Microplastic (MP) pollution is an important challenge for human life which has consequently affected the natural system of other organisms. Mismanagement and also careless handling of plastics in daily life has led to an accelerating contamination of air, water and soil compartments with MP. Under estuarine conditions, interactions with suspended particulate matter (SPM) like fine sediment in the water column play an important role on the fate of MP. Further studies to better understand the corresponding transport and accumulation mechanisms are required. This paper aims at providing a new modeling approach improving the MP settling velocity formulation based on higher suspended fine sediment concentrations, as i.e. existent in estuarine turbidity zones (ETZ). The capability of the suggested approach is examined through the modeling of released MP transport in water and their interactions with fine sediment (cohesive sediment/fluid mud). The model results suggest higher concentrations of MP in ETZ, both in the water column as well as the bed sediment, which is also supported by measurements. The key process in the modeling approach is the integration of small MP particles into estuarine fine sediment aggregates. This is realized by means of a threshold sediment concentration, above which the effective MP settling velocity increasingly approaches that of the sediment aggregates. The model results are in good agreement with measured MP mass concentrations. Moreover, the model results also show that lighter small MP particles can easier escape the ETZ towards the open sea.